2005
DOI: 10.1016/s1808-8694(15)31253-2
|View full text |Cite
|
Sign up to set email alerts
|

Revision about hearing loss in the Alport's syndrome, analyzing the clinical, genetic and bio-molecular aspects

Abstract: Alport Syndrome is a genetic disorder characterized by hematuria, which often leads to renal failure. It may also be accompanied by extra-renal alterations, such as: sensorineural hearing loss, and ocular abnormalities. Dominant forms related to the X chromosome and caused by mutations in the locus COL4A5 have been described, as well as an autossomic recessive form resulting from mutations in the locus COL4A3 or COL4A4. An autossomic dominant type of AS has also been reported. The disease is caused by changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
17
2
1
Order By: Relevance
“…Furthermore, pathology at the level of the basilar membrane could be responsible for the good speech recognition scores seen in the present family, which is also found in Alport syndrome. (Moon et al, 2008;Alves and De Quintanilha Ribeiro, 2005) Results of the audiometric evaluation also indirectly support the hypothesis of improper motion of the basilar membrane in patients with MWS. Suprathreshold measures such as DL f and gap detection were within the normal range or at least close to data obtained in two groups of patients with known abnormalities of the tectorial membrane (Plantinga et al, 2007;De Leenheer et al, 2004).…”
Section: Pathogenesis Of Hearing Impairment In Mwsmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, pathology at the level of the basilar membrane could be responsible for the good speech recognition scores seen in the present family, which is also found in Alport syndrome. (Moon et al, 2008;Alves and De Quintanilha Ribeiro, 2005) Results of the audiometric evaluation also indirectly support the hypothesis of improper motion of the basilar membrane in patients with MWS. Suprathreshold measures such as DL f and gap detection were within the normal range or at least close to data obtained in two groups of patients with known abnormalities of the tectorial membrane (Plantinga et al, 2007;De Leenheer et al, 2004).…”
Section: Pathogenesis Of Hearing Impairment In Mwsmentioning
confidence: 63%
“…Since ossification did not occur in other parts of the temporal bone, an otosclerotic pathogenesis was excluded (Muckle and Wells, 1962). The cause of hearing impairment in MWS is still unknown, but the basilar membrane could be involved in the pathogenesis of hearing impairment, as is the case in the pathogenesis of Alport syndrome (Moon et al, 2008;Alves and De Quintanilha Ribeiro, 2005;Merchant et al, 2004). The structurally defective basement membrane in Alport syndrome probably provides inadequate adhesion between the organ of Corti and the underlying basilar membrane.…”
Section: Pathogenesis Of Hearing Impairment In Mwsmentioning
confidence: 99%
“…42 Furthermore, mutations in the COL4A3-5 genes cause Alport syndrome, an inherited disorder showing progressive nephropathy, ocular abnormalities, and sensorineural hearing loss. 43 In contrast, COL4A3-knockout mice did not present with an uniformly elevated hearing threshold, since only three out of 12 animals studied showed a significantly altered ABR. 44 In a parallel study, thickening of the strial BM was observed in COL4A3-null mice at the ultrastructural level; however, a slight shift in auditory threshold shift was reported only in some older animals.…”
Section: Profound Alterations In the Organ Of Corti From Ddr1-null Micementioning
confidence: 88%
“…Disease in both organ systems can be related to mutations in these pathways, including glomerulopathies, tubulopathies, ciliopathies and congenital anomalies of the kidney and urinary tract . Examples are listed in Table . Urinalysis is recommended where there is delayed onset of SNHL, progressive SNHL or if there is a family history of renal disease as listed above.…”
Section: Resultsmentioning
confidence: 99%